Strategi Kolaboratif Tri Pusat Pendidikan dalam Menangani Dekadensi Akhlak Siswa Studi Kasus di MTS Alwashliyah 30 Pematang Guntung - Rahmawati Rahmawati; Yulia Warda; Nurul Hidayah (HIBRUL ULAMA, 2025)
Student moral decline requires educational responses that extend beyond school and systematically involve families and the community. This study aims to describe a Tri-Center Education (school–family–community) collaborative strategy in addressing students’ moral decline at MTs Alwashliyah 30 Pematang Guntung. The research employed a qualitative case-study design. Data were collected through participant observation, semi-structured interviews, and documentation, involving school leaders, Islamic education teachers, students, parents, and community/committee figures as key informants. Data analysis followed an interactive process comprising data reduction, data display, and conclusion drawing/verification, supported by methodological triangulation to enhance credibility. The findings indicate that students’ Islamic moral development was strengthened through the integration of character values in learning activities, daily religious habituation, educative disciplinary regulations, reinforcement of the PPRA program, and character-oriented extracurricular activities. Collaboration across school–parents–community was operationalized through two-way communication, coaching forums, community engagement in religious activities, and persuasive social monitoring. Overall, the collaborative strategy facilitated positive behavioral change and helped establish a consistent moral-development ecosystem for students.